Analysis of Ag2+ and Cu2+ electroplating on the aluminum layer thickness level: A reanalysis - Aming Sungkowo; Yanuar Zulardiansyah Arief; Rosyid Ridlo Al-Hakim (University of Science and Computer Technology, 2022)
We reanalyze the effect of silver (Ag2+) and copper (Cu2+) coating solutions for the thickness of the layer on aluminum (Al) materials with increased electrical currents 0.4A, 0.8A, 1A, 1.2A, and 1.4A and increased thickness layer (10µm, 20µm, 30µm, 40µm, and 50µm), as well as the previous study was conducted. We used the electroplating method and thickness test, as well as the Brinell hardness test for both coating solutions. The results show statistically significant (p-value < 0.05, one-tailed) between high electric current and aluminum (Al) coating process with silver (Ag2+) and copper (Cu2+), as well as silver (Ag2+), get the faster coating process time. The Brinell hardness test shows a statistically significant difference (p-value < 0.05, one-tailed) between the high thickness layer and HB value (Ag-coated and Cu-coated).